Kinerja Pegawai dalam Pelayanan Publik di Kecamatan Selaru Kabupaten Kepulauan Tanimbar - Laiyan, Susi Susanti; Alhamid, Rugaya; Waisapy, Jeanly (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the performance of employees in public service at Selaru District, Tanimbar Islands Regency. The type of research used in this study is qualitative research. The author evaluates employee performance indicators in public service through observation techniques, interview techniques, and documentation techniques. Based on the research findings, the quality of service in Selaru District can be measured by public satisfaction. Although most residents consider the employees' service to be fairly good, there are still complaints regarding long service times. Factors hindering employee performance include a lack of facilities such as computers and low service quality. Punctuality is also an issue, as employees often do not arrive on time, and service speed needs improvement. Service effectiveness is further affected by low work discipline, caused by a lack of leadership firmness and weak sanctions for employees who are late, leave their workplace without a clear reason, or leave early. Additionally, in terms of independence, the government and district head are expected to be more proactive in providing services and meeting the needs of the community quickly and responsively to enhance the effectiveness of public service in Selaru District.